Constructing managerial manoeuvring space in contradictory contexts. Issue 4 (August 2021) - Filstad, Cathrine; Olsen, Trude Høgvold; Karp, Tom
Abstract: This paper discusses manoeuvring space and demonstrates how autonomy, power and discretion need to be understood as constructed and integrated behaviours where managers manoeuvre between dilemmas in their own management practices. Twenty-seven Norwegian police managers were shadowed and interviewed. We found that constructions of manoeuvring space presupposed that managers balanced dilemmas. We identified three different strategies through which managers constructed manoeuvring space by navigating between dilemmas and actively constructing demands and constraints. These strategies were (1) decoupling, (2) sensegiving and (3) strategic positioning. Our findings add to the managerial discretion literature, arguing that constructions of manoeuvring space are central to managers' development and to how they create opportunities and possibilities to make choices that balance conflicting dilemmas in contradictory contexts.